Pengaruh Literasi Keuangan Digital dan Kesadaran Keamanan Transaksi terhadap Perilaku Penggunaan Dompet Digital pada Siswa MAN 1 Muaro Jambi - Ayustika Feronika; Muhammad Bristi; Rimka Syafri; Laura Pramadita; Joni Cristina (Jurnal Pengabdian dan Ekspalanasi Nusantara, 2026)
The rapid development of digital financial technology has transformed transaction behavior among Generation Z, particularly through the increasing use of digital wallets and QRIS-based payment systems. However, the high adoption of digital payment services has not always been accompanied by adequate digital financial literacy and transaction security awareness. This community service program aimed to improve digital financial literacy and strengthen transaction security awareness among students of MAN 1 Muaro Jambi to encourage safer and more responsible digital wallet usage behavior. The implementation method employed a participatory and educational approach consisting of five stages: socialization, training, technology implementation, mentoring and evaluation, and program sustainability. The activities included interactive learning sessions, case studies, simulations of digital transactions, and practical exercises on securing digital accounts and protecting personal data. Program evaluation was conducted through pre-test and post-test assessments to measure changes in participants’ understanding and behavior. The results indicated improvements in participants’ knowledge of digital financial management, awareness of transaction security risks, and ability to apply safer digital payment practices. Students demonstrated greater awareness of managing expenditures, identifying potential digital fraud, and protecting personal information during financial transactions. Overall, the program contributed to strengthening digital financial competence and promoting sustainable financial behavior among students in response to the ongoing digital economic transformation.